Language and Identity: A Reappraisal of Negeri Sembilan Malay Language - Idris Aman; Mohammad Fadzeli Jaafar; Norsimah Mat Awal (Kajian Malaysia, 2019)
Negeri Sembilan, as one of the states in Malaysia, has been greatly influenced by the Minangkabau culture, in particular the Perpatih custom which led to the socalled misunderstanding that Negeri Sembilan Malay language (NSML) resembles or is similar to the Minangkabau language. This article aims to describe the distinctive phonological features of Negeri Sembilan language to mark its identity and therefore prove that it is free from the Minangkabau linguistic influence. This study utilises the Swadesh word list of 100 words to test pronunciation. Thirty informants were involved and they are speakers of the Negeri Sembilan Malay language and speakers of the Minangkabau language both in Malaysia and Sumatera. The research was conducted in Kuala Pilah, Rembau, and Beranang in Malaysia, while in Indonesia the data was collected in Paya Kumbuh, Bukit Tinggi, and Padang. Based on the 100 words tested, this study observed 17 pronunciation patterns in Negeri Sembilan language that are distinct from the Minangkabau language, specifically they are 10 vowel sounds patterns and 7 consonant sounds patterns. From these 17 patterns, 13 only occur in NSML and the remaining 4 patterns occur in both NSML and the Minangkabau language. Hence, it can be concluded that the Negeri Sembilan language has its own distinctive phonological identity, thus distinguishing it from the Minangkabau linguistic features.